Analysis of the Implementation of Regent's Regulation Number 115 of 2017 concerning Technical Guidelines for the Implementation of Village Head Elections in Banyuasin Regency (Case Study: Kenten Laut Village, Talang Kelapa District, Banyuasin Regency) - Citra Iasha (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
This study aims to analyze the implementation of technical guidelines for selecting village heads in Kenten Laut Village, Talang Kelapa District, Banyuasin Regency and to analyze factors that hinder the implementation of technical guidelines for village head elections in Kenten Laut Village, Talang Kelapa District, Banyuasin Regency. The research method used is a qualitative method. Data was collected by means of observation, interviews, and literature study. Based on these findings, the implementation of the regulation will be successful if: (1) there is smooth communication, (2) the availability of resources needed in implementing the policy, (3) good attitude disposition, (4) organizational structure, from the implementers to the successful implementation policies in the field. Based on the results of the research and discussion, the authors can draw conclusions including the following: The implementation of Regent Regulation Number 115 of 2017 concerning Technical Instructions for the Implementation of Village Head Elections in Banyuasin Regency has been going well, it can be seen from community socialization in the form of communication, resources, disposition and structure. bureaucracy. The inhibiting factors for the implementation of Regent's Regulation Number 115 of 2017 concerning Technical Guidelines for the Implementation of Village Head Elections in Banyuasin Regency, Talang Kelapa District, lack of community awareness or there are still people who do not want to participate.